2019
DOI: 10.1080/24750573.2019.1673944
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of selective serotonin reuptake inhibitors (SSRIs) on cornea and lens density in patients with depression

Abstract: PURPOSE: To investigate the effects of SSRIs on cornea and lens density, intraocular pressure (IOP) and anterior chamber parameters, including anterior chamber volume (ACV), anterior chamber depth (ACD), corneal volume (CV) and central corneal thickness (CCT), in patients with depression during a three-month follow-up period. METHOD: In this prospective study, 31 total patients, who were prescribed SSRIs for depression, were recruited. Sertraline, 50 mg/daily, was given to ten patients; 11 received Escitalopra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Longer-term and larger population studies are needed to observe this effect. 15 Limitations of this study; the findings of patients taking antidepressants before and after treatment were not compared, due to the retrospective nature of this study, the need for research in larger populations, and longer follow-up to observe the effect. The strengths of this study are quantitative evaluation with corneal topography and specular microscopy in addition to ocular surface examination, it includes different agent subgroups, and the examination of more than one agent with similar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Longer-term and larger population studies are needed to observe this effect. 15 Limitations of this study; the findings of patients taking antidepressants before and after treatment were not compared, due to the retrospective nature of this study, the need for research in larger populations, and longer follow-up to observe the effect. The strengths of this study are quantitative evaluation with corneal topography and specular microscopy in addition to ocular surface examination, it includes different agent subgroups, and the examination of more than one agent with similar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Becker et al concluded that SSRI therapy does not alter the risk of cataracts [124]. Given these inconsistent findings, providers should recommend regular eye examinations for patients on SSRIs [125].…”
Section: Cataractsmentioning
confidence: 98%